“Virtualización de servidores mediante el uso de las herramientas VMWARE WORKSTATION 9.0 y CITRIX XENSERVER 6.2 y levantamiento de servicios en la plataforma windows server 2012, en el laboratorio de redes de la Universidad Técnica de Cotopaxi, ciudad de Latacunga, provincia de Cotopaxi, en el periodo 2013-2014” - López Uribe, Saúl Fabián (2014)
Server virtualization is an aid in the network laboratory of the Technical University of Cotopaxi, which will offer a higher level and lower high costs of money, it is a platform where computing, network, storage resources will be optimized in a single system, management and infrastructure management. This research work consists of an analysis of the main tools to use such as VMware Workstation 9.0 and Citrix XenServer 6.2, these tools will help us simulate the operation of a real machine with all its components and thus provide all the necessary resources for its operation, since this will offer better stability and management in the control of network information. A guide will be offered as a manual for the proper use of the tools to virtualize step by step, increasing the use of server resources since this is essential to run multiple applications and operating systems, as well as guaranteeing security and control in the laboratory.